Pengaruh User-Generated Content pada Platform Tiktok terhadap Purchase Intention Produk Aquviva - Steven Avrillio Andika Putra; Indah Handaruwati (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This research analyzes the influence of User-generated content on purchase intention toward Aquviva bottled drinking water among TikTok users who have watched promotional content from the account @cal0npengusaha. This study shows how consumer opinions are being influenced by social media more and more. and purchasing behaviour, particularly through user-created content that is often perceived as more real and approachable than traditional advertising. The study focuses on three perception variables related to User-generated content: perceived credibility, perceived usefulness, and perceived risk. This research uses A quantitative and associative research design. An online questionnaire with a Likert scale was used to collect data from 40 TikTok users who had seen user-generated content on Aquviva. The sampling technique applied was Purposive sampling. Following the validation, reliability, and classical assumption tests, the data was evaluated using multiple linear regression. The results indicate that perceived credibility and perceived risk do not significantly influence purchase intention, as their significance values exceed 0.05. In contrast, perceived usefulness has a strong and significant effect, highlighting that informative and beneficial content plays a key role in attracting consumers’ interest in a product. Simultaneously, the three variables significantly affect purchase intention, explaining 67.6% of its variance, implying that improving content usefulness is crucial for increasing consumers’ purchase intentions.